Analysis of Perception and Interrelationship between Teachers’ Interpersonal Communication and Students’ Learning Motivation - Budiarti, Retni Sulistiyoning; Anita, Desi; Wicaksana, Ervan Johan; Huda, Nizlel (FKIP Universitas Lampung, 2022)
This study aims to analyze the relationship between the teacher's interpersonal communication skills and the learning motivation of class X MIA SMAN 11 Jambi City in the 21st Century Learning Mushroom Material. numerical data (numbers) processed by statistical methods. The population of this study were all students of class X MIA SMA Negeri 11 Jambi City as many as 132 students. The results of the Validity and Reliability Test of the Teacher Interpersonal Communication Ability Questionnaire were seen from the SPSS test results on the cronbach alpha value of 0.92 where the questionnaire was declared reliable or consistent because the value was more of 0.60. Furthermore, the results of the validity and reliability of the Student Learning Motivation Questionnaire were seen from the results of the SPSS test at the cronbach alpha value of 0.91 where the questionnaire was declared reliable or consistent because the value was more than 0.60. Keywords: interpersonal communication, student learning motivation, 21st century, fungi. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp805-820